Fast separation of selected cathinones and phenylethylamines by supercritical fluid chromatography - Pauk, Volodymyr; Žihlová, Veronika; Borovcová, Lucie; Havlíček, Vladimír; Schug, Kevin; Lemr, Karel (Journal of chromatography. A, Including electrophoresis and other separation methods, 2015)
The chromatographic behaviour of eleven synthetic cathinones and four phenylethylamines under supercritical/subcritical fluid conditions was investigated. Four stationary phases with sub-2μm particles (Waters Acquity UPC(2) BEH silica, BEH 2-ethylpyridine, CSH Fluoro-Phenyl, and HSS C18SB) were evaluated in terms of isomer resolution, chromatographic peak shape, and analysis time. Methanol, water, formic acid, ammonium hydroxide, ammonium acetate, and ammonium formate were mixed with carbon dioxide to test their influence on analyte retention and peak shapes. Methanol and ammonium cations were essential for successful separations. Efficient separations of four isomeric pairs (R>1), and most of the remaining analytes, were achieved in less than 3.3min on BEH and Fluoro-Phenyl columns with gradient of methanolic ammonium hydroxide in CO2. Drugs were detected by positive electrospray ionization-triple quadrupole mass spectrometry in selected reaction monitoring mode. Added detection specificity and faster separation of isomers on the BEH column using a steep gradient and high flow rate reduced analysis time of the mixture of 15 drugs to 1.6min.
Keywords: superkritická fluidní chromatografie; Methanol; Alkaloids; fenethylaminy; Chemistry Techniques, Analytical; chemické techniky analytické; Phenethylamines; Chromatography, Supercritical Fluid; alkaloidy; methanol